Identification of Sox8 and Ndp as Novel Targets of the Hedgehog Signaling Pathway in the Retina - McNeill, Brian (Université d'Ottawa / University of Ottawa, 2012)
During embryonic development, the Hedgehog (Hh) signaling pathway plays an important role in the growth and patterning of numerous tissues and organs. In the developing retina, Hh signaling regulates the proliferation and differentiation of retinal progenitor cells (RPC) through mechanisms that are not completely understood. The principal downstream mediators of the Hh pathway are the Gli transcription factors (Gli1-3), which regulate the expression of target genes responsible for the effects of the Hh pathway on RPC. The network of genes targeted by this pathway in neural progenitor cells however, remains unknown. The objective of this thesis was to identify and characterize novel targets of Hh/Gli during retinal development. Using a computation approach, 390 genes were identified as having at least one conserved Gli binding motif within the vicinity of the coding sequence between humans and mice. During validation, I demonstrate that 30 of 46 selected targets were modulated in response to Hh pathway activation in either E14.5 and/or P0.5 retinal explants and that the induction of 25 of these were significantly different between the two developmental stages. Included in this list of Hh-modulated genes were Sox8 and Ndp, two highly inducible genes that are direct targets of Gli2. Functionally, I was unable to determine a role for Sox8 during retinal development which could reflect compensation by the closely related Sox9 and Sox10 genes. Ndp on the other hand was found to be sufficient and required for Hh mediated induction in progenitor cell proliferation and cell fate determination. Therefore, in this thesis Hh target genes have been identified which could provide some insight into the mechanisms that are responsible for the cellular outcome of a response to the pathway.
Keywords: retina; development; Sonic hedgehog; proliferation